Optimization of Cooking Method and Cooking Duration for Enhancing the Quality of Pangasius (Pangasius hypophthalmus) Fish Nuggets - Alhanannasir Alhanannasir; Suyatno Suyatno; Alfando Wedyan Pratama (Universitas Muhammadiyah Palembang, 2026)
Fish nuggets are a popular processed food product due to their high nutritional value and convenience. This study aimed to determine the effect of cooking method and duration on the chemical and organoleptic characteristics of nuggets made from *Pangasius hypophthalmus* (Siamese catfish). A factorial Randomized Block Design (RBD) was employed, involving two treatment factors: cooking method (boiling and steaming) and cooking duration (25, 45, and 65 minutes). The parameters observed included protein content, moisture content, color, aroma, taste, and springiness. The results indicated that both cooking method and duration significantly affected the protein content, moisture content, and organoleptic characteristics of the catfish nuggets. Steaming for 25 minutes (P2W1) yielded the highest protein content (21.80%) and the lowest moisture content (47.639%), as well as the highest scores for color (4.32), aroma (3.88), and taste (4.40). The highest springiness score (3.96) was obtained with the 45-minute steaming treatment (P2W2). Steaming for 25 minutes was identified as the optimal treatment for producing catfish nuggets with the best nutritional quality and sensory acceptance.